A FIQH MUAMALAH PERSPECTIVE ON THE USE OF CLOUD COMPUTING IN MSME FINANCIAL MANAGEMENT IN SRAGEN REGENCY - Farid, Ilham Rosyid Miftahul; Krismono, Krismono; Syahmirwan, Syahmirwan (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research Aims: This study aims to examine the adoption of cloud computing technology in MSME financial management in Sragen Regency from the perspective of fiqh muamalah and assess its compatibility with Islamic sharia principles. Design/Methodology/Approach: This research adopts a qualitative case study approach. Data were collected through in-depth interviews with MSME practitioners, direct observations, and literature studies on Islamic financial jurisprudence. The analysis examines Islamic contract principles including ijarah (leasing), wakalah (agency), and syirkah (partnership), alongside aspects of data ownership, security, and sharia compliance. Research Findings: The findings indicate that cloud computing significantly enhances operational efficiency and financial transparency in MSME management. However, implementation must adhere to Islamic principles of fairness, transparency, and avoidance of riba (usury) and gharar (excessive uncertainty). Cloud computing services can be legitimately adopted by MSMEs when structured according to sharia-compliant frameworks. Theoretical Contribution/Originality: This study contributes to Islamic business literature by integrating contemporary digital technology with classical fiqh muamalah principles. It provides novel insights into reconciling cloud computing with sharia values, offering a theoretical framework for technology adoption in Islamic-oriented business environments. Practitioners/Policy Implications: The results recommend that MSMEs select cloud service providers offering sharia-compliant contracts. Policymakers should develop regulatory frameworks supporting Islamic-compliant cloud computing models. Technology providers are encouraged to design solutions tailored to Islamic principles, facilitating wider adoption among Muslim entrepreneurs. Research Limitations/Implications: The qualitative case study approach and geographic focus on Sragen Regency may limit generalizability. Future research should employ mixed-methods designs across diverse regions, explore additional variables such as digital literacy and cost-benefit analysis, and develop standardized sharia-compliant cloud computing models for MSME financial management.